Micro-encapsulated and colonic-release sodium butyrate modulates gut microbiota and improves abdominal pain in patients with symptomatic uncomplicated diverticular disease - Tursi, Antonio; Procaccianti, Giorgia; De Bastiani, Rudi; Turroni, Silvia; D’Amico, Federica; Allegretta, Leonardo; Antonino, Natale; Baldi, Elisabetta; Casamassima, Carlo; Casella, Giovanni; Ciuffi, Mario; De Bastiani, Marco; et al. (Frontiers in Medicine, 2025)
The role of gut microbiota (GM) in the pathogenesis of Symptomatic Uncomplicated Diverticular Disease (SUDD) remains controversial. Here, we assessed the efficacy of a butyrate formulation in modulating GM and abdominal pain in patients with SUDD. A retrospective study was conducted in patients with SUDD who were treated with a delayed- and colonic-release formulation of butyrate (two capsules bid, for a total dose of 400 mg butyrate) for 3 months. GM was profiled before (T0) and after 90 days of treatment (T2) using 16S rRNA amplicon sequencing. The primary endpoint was change in GM at T2; secondary endpoints were reduction in abdominal pain severity according to VAS (Visual Analog Scale, 0: absence; 10: maximum severity) at T1 (45 days) and T2, stool characteristics according to the Bristol stool form scale at T0, T1 and T2, and safety of treatment. Fifty-nine patients with SUDD (59.3% male; median age 65.5 years, interquartile range 55–71 years) completed treatment. The butyrate formulation increased GM diversity and resulted in several compositional changes that were closely related to baseline abdominal pain severity. Regarding secondary endpoints, abdominal pain decreased significantly over time, while the Bristol stool form scale did not. Mild adverse events were recorded in 3 (5.08%) patients. This study showed that a microencapsulated and colonic-release formulation of butyrate favorably modulates GM and reduces abdominal pain in patients with SUDD.